2015
DOI: 10.3928/23258160-20150213-24
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Central Retinal Artery Occlusion Associated With Herpes Simplex Virus–Associated Acute Retinal Necrosis and Meningitis: Case Report and Literature Review

Abstract: A 60-year-old woman with a history of recurrent headaches and blurred vision but otherwise healthy presented to an ophthalmologist with bilateral optic disc edema. Intravenous methylprednisonlone was administered because of a concern for optic neuritis. The patient’s vision declined to hand motions level in both eyes and a subsequent evaluation revealed bilateral acute retinal necrosis with bilateral central retinal artery occlusions. Aqueous humor polymerase chain reaction analysis was positive for herpes sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…The spinal tap fluid only revealed an increased lymphocyte count, with all PCR analysis negative for viral encephalitis. Brain MRI, as in several of the reports, revealed a hypersignal of the optic pathway in the T2 and Flair-weighted images 8. The diagnosis was confirmed by PCR analysis for HSV-1 of the vitreous and aqueous humour, both sterile ocular fluids.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The spinal tap fluid only revealed an increased lymphocyte count, with all PCR analysis negative for viral encephalitis. Brain MRI, as in several of the reports, revealed a hypersignal of the optic pathway in the T2 and Flair-weighted images 8. The diagnosis was confirmed by PCR analysis for HSV-1 of the vitreous and aqueous humour, both sterile ocular fluids.…”
Section: Discussionsupporting
confidence: 64%
“…Unilateral disease is more commonly reported in cases of ARN, nevertheless, bilateral involvement can occur in 1/3 of patients, 1–6 weeks after the first eye. Bilateral presentation of ARN is more predominant in neonates and immunosuppressed individuals than in immunocompetent patients 8. However, in our patient, none of the studies performed revealed any primary or acquired immunosuppressive disease that could justify such an aggressive evolution.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Despite aggressive therapy including hospitalization for intravenous antivirals and repeated intravitreal foscarnet and ganciclovir injections, bilateral severe vision loss to hand motions level developed at final follow-up. 56 Other reports of severe cases of herpetic retinitis following corticosteroids include patients with presumptive optic neuritis, optic neuropathy, and seventh nerve palsy of unclear etiology. 57,58,59 ARN has also been described in patients treated with intravitreal triamcinolone for choroidal neovascular membranes.…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…Weissman et al reported a patient with suspected optic neuritis who received intravenous solumedrol and later developed bilateral central retinal artery occlusions associated with fulminant bilateral acute retinal necrosis and meningitis. 15 Some uveitis specialists have advocated local corticosteroid in the setting of cystoid macular edema after resolution of active retinitis; however, the potential for retinitis recurrence should be considered.…”
Section: Corticosteroid Usementioning
confidence: 99%